2010
DOI: 10.1038/aps.2010.192
|View full text |Cite
|
Sign up to set email alerts
|

Mixed micelles loaded with silybin-polyene phosphatidylcholine complex improve drug solubility

Abstract: Aim: To prepare a novel formulation of phosphatidylcholine (PC)-bile salts (BS)-mixed micelles (MMs) loaded with silybin (SLB)-PC complex for parenteral applications. Methods: SLB-PC-BS-MMs were prepared using the co-precipitation method. Differential scanning calorimetry (DSC) analysis was used to confirm the formation of the complex and several parameters were optimized to obtain a high quality formulation. The water-solubility, drug loading, particle size, zeta potential, morphology and in vivo properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…Thus, the optimized mass ratio of PC to SDC got from the experiment basically accorded with the above discussion. The micro-morphology showed that the CUR-PC-SDC-MMs prepared through thin film dispersed method were spherical, which is consistent with the previous report (Duan et al, 2011). In terms of the aggregate structure, lots of researchers have studied on bile salt/PC mixed micelles by a series of methods such as static and dynamic light scattering, small-angle neutron scattering, small angle x-ray scattering and cryo-TEM (Long et al, 1994).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Thus, the optimized mass ratio of PC to SDC got from the experiment basically accorded with the above discussion. The micro-morphology showed that the CUR-PC-SDC-MMs prepared through thin film dispersed method were spherical, which is consistent with the previous report (Duan et al, 2011). In terms of the aggregate structure, lots of researchers have studied on bile salt/PC mixed micelles by a series of methods such as static and dynamic light scattering, small-angle neutron scattering, small angle x-ray scattering and cryo-TEM (Long et al, 1994).…”
Section: Discussionsupporting
confidence: 85%
“…High DL% and EE% maybe ascribed to the potential mechanization that PC and SDC reveal the strongest bonding force (Duan et al, 2011) when the mass ratio is at 0.264. The aggregation system of PCs alone is liquid crystalline bilayer structure instead of micelle, which is difficult to be digested (Tang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of alternative technologies are being developed to overcome the drawbacks associated with poor aqueous solubility, for example, including use of surfactants [3], micronization [4], inclusion complexation [5] and solid dispersion [6]. Among these solid dispersion has gained importance as a promising approach, as the other methods suffer from limitation like size reduction by micronization, results in the formation of surface charge on particles which restrict their flow and exhibit poor flow properties [7].…”
Section: Introductionmentioning
confidence: 99%
“…19 Due to their good physiological compatibility and excellent solubilizing capacity, bile salt micelles and derived mixed systems have been intensively investigated as drug-carrier systems. [20][21][22] Previous investigations into bile salt/phospholipid MMs has mainly focused on the solubilization of insoluble drugs, 18,[23][24][25] structural identification, 26 physicochemical properties, 27 and transmembrane characteristics; 17 however, bile salt/ phospholipid MMs may also be good candidates for oral delivery of poorly water-soluble drugs.…”
Section: Introductionmentioning
confidence: 99%